Formazione e-learning degli insegnanti e pensiero creativo - Gaetano Domenici; Valeria Biasi; Anna Maria Ciraci (LED Edizioni Universitarie, 2014)
E-learning Teacher's Training and Creative Thinking This paper deals with the complex theme of assessing teachers' professional competencies. It illustrates an empirical study conducted in 2012/2013 by Domenici, Biasi and Ciraci, for the Department of Education of «Roma Tre» University. The study involved 287 inservice primary school teachers in the Lazio region who graduated in Education through «Roma Tre» University's e-learning platform. It aimed to assess whether the distancelearning degree course the teachers had completed had increased their professional skills and in what directions. We used a specific on-line instrument, the CDVR questionnaire, in order to evaluate their teaching and relational competencies. The results show that the above e-learning university courses, conducted through an active didactics based on selfassessment and on innovative strategies for simulation environments, produced an increase in the teacher's perception of educational and evaluative skills, and in the teacher's perception of the ability to understand others, together with a greater mental flexibility, which means creativity. These active teaching methods, thanks to new technologies, have promoted the development of attitudes underlying the expert teacher, who is mentally flexible and creative in finding novel solutions to many educational problems. A better understanding of the challenges along with improved communication skills (thanks to better teaching and evaluation strategies and more in-depth psychological knowledge) led to a special effect on the ability to interact and develop a positive attitude in the context of the educational relationship, a functional attitude to enhance the learning process and thus the achievement of the learning outcomes pursued.